Building a 'Virtual Library': continuing a global collaboration to strengthen research capacity within Nepal and other low- and middle-income countries - Catherine E. Elmore; Sandhya Chapagain Acharya; Soniya Dulal; Flannery Enneking-Norton; Pawan Kumar Hamal; Regina Kattel; Martha A. Maurer; Damodar Paudel; Bishnu Dutta Paudel; Ramila Shilpakar; Deepak Sundar Shrestha; Usha Thapa; et al. (Taylor & Francis Group, 2022)
To fill the gap in health research capacity-building efforts, we created the 'Virtual Library' (VL) - a web-based repository of context-relevant resources for health researchers in low- and middle-income countries (LMICs). This paper describes the participatory process used to systematically develop the VL, and describes how our interprofessional team - representing both an LMIC (Nepal) and a high-income country (HIC) (USA, US) - engaged in shared meaning-making. A team of researchers and clinicians representing a range of subdisciplines from Nepal and the US created a replicable search strategy and standardized Resource Screening Guide (RSG) to systematically assess resources to be included within the VL. Descriptive methods were used to summarize findings from the RSG and lessons learned from the collaborative process. Collectively, 14 team members reviewed 564 potential resources (mean = 40, SD = 22.7). Mean RSG score was 7.02/10 (SD = 2). More than 76% of resources met each of the four quality criteria (relevant; reputable, accessible; understandable). Within the published VL, 298 resources were included, organized by 15 topics and 45 sub-topics. Of these, 223 resources were evaluated by the RSG; 75 were identified by team member expertise. The collaborative process involved regular meetings, iterative document revisions, and peer review. Resource quality was better than expected, perhaps because best practices/principles related to health research are universally relevant, regardless of context. While the RSG was essential to systematize our search and ensure reproducibility, team member expertise was valuable. Pairing team members during peer-review led to bi-directional knowledge sharing and was particularly successful. This work reflects a highly collaborative global partnership and offers a model for future health research capacity-building efforts. We invite engagement with the Virtual Library <https://lmicresearch.org> as one supportive pillar of infrastructure to develop individual and institutional research capacity.